De novo Analysis of the Epiphytic Transcriptome of the Cucurbit Powdery Mildew Fungus Podosphaera xanthii and Identification of Candidate Secreted Effector Proteins. - David Vela-Corcía; Rocío Bautista; Antonio de Vicente; Pietro D Spanu; Alejandro Pérez-García (PLoS ONE)
The cucurbit powdery mildew fungus Podosphaera xanthii is a major limiting factor for cucurbit production worldwide. Despite the fungus's agronomic and economic importance, very little is known about fundamental aspects of P. xanthii biology, such as obligate biotrophy or pathogenesis. To design more durable control strategies, genomic information about P. xanthii is needed. Powdery mildews are fungal pathogens with large genomes compared with those of other fungi, which contain vast amounts of repetitive DNA sequences, much of which is composed of retrotransposons. To reduce genome complexity, in this work we aimed to obtain and analyse the epiphytic transcriptome of P. xanthii as a starting point for genomic research. Total RNA was isolated from epiphytic fungal material, and the corresponding cDNA library was sequenced using a 454 GS FLX platform. Over 676,562 reads were obtained and assembled into 37,241 contigs. Annotation data identified 8,798 putative genes with different orthologues. As described for other powdery mildew fungi, a similar set of missing core ascomycete genes was found, which may explain obligate biotrophy. To gain insight into the plant-pathogen relationships, special attention was focused on the analysis of the secretome. After this analysis, 137 putative secreted proteins were identified, including 53 candidate secreted effector proteins (CSEPs). Consistent with a putative role in pathogenesis, the expression profile observed for some of these CSEPs showed expression maxima at the beginning of the infection process at 24 h after inoculation, when the primary appressoria are mostly formed. Our data mark the onset of genomics research into this very important pathogen of cucurbits and shed some light on the intimate relationship between this pathogen and its host plant.